Calculated line lists for H216O and H218O with extensive comparisons to theoretical and experimental sources including the HITRAN2016 database. (January 2020) - Conway, Eamon K.; Gordon, Iouli E.; Kyuberis, Aleksandra A.; Polyansky, Oleg L.; Tennyson, Jonathan; Zobov, Nikolai F.
Highlights: New dipole moment surface provides excellent calculated intensities. Calculated line lists agrees very well with many experimental and theoretical sources. Transition intensities are sensitive to subtle changes in the potential. Further work is required in the visible. Abstract: New line lists are presented for the two most abundant water isotopologues; H2 16 O and H2 18 O. The H2 16 O line list extends to 25710 cm − 1 with intensity stabilities provided via ratios of calculated intensities obtained from two different semi-empirical potential energy surfaces. The line list for H2 18 O extends to 20000 cm − 1 . The minimum intensity considered for all is 10 − 30 cm molecule − 1 at 296 K, assuming 100% abundance for each isotopologue. Fluctuation of calculated intensities caused by changes in the underlying potential energy are found to be significant, particularly for weak transitions. Direct comparisons are made against eighteen different sources of line intensities, both experimental and theoretical, many of which are used within the HITRAN2016 database. With some exceptions, there is excellent agreement between our line lists and the experimental intensities in HITRAN2016. In the infrared region, many H2 16 O bands which exhibit intensity differences of 5–10% between to the most recent 'POKAZATEL' line list (Polyansky et al., [Mon. Not. Roy. Astron. Soc. 480, 2597 (2018)] and observation, are now generally predicted to within 1%. For H2 18 O, there are systematic differences in the strongest intensities calculated in this work versus those obtained from semi-empirical calculations. In the visible, computed cross sections show smaller residuals between our work and both HITRAN2016 and HITEMP2010 than POKAZATEL. While our line list accurately reproduces HITEMP2010 cross sections in the observed region, residuals produced from this comparison do however highlight the need to update line positions in the visible spectrum of HITEMP2010. These line lists will be used to update many transition intensities and line positions in the HITRAN2016 database.